2013
DOI: 10.1007/s11357-013-9584-1
|View full text |Cite
|
Sign up to set email alerts
|

Explosive type of moderate-resistance training induces functional, cardiovascular, and molecular adaptations in the elderly

Abstract: Current recommendations aimed at reducing neuromuscular and functional loss in aged muscle have identified muscle power as a key target for intervention trials, although little is known about the biological and cardiovascular systemic response in the elderly. This study investigated the effects of 12 weeks of low-frequency, moderate-intensity, explosive-type resistance training (EMRT) on muscle strength and power in old community-dwelling people (70-75 years), monitoring functional performance linked to daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 45 publications
4
65
0
Order By: Relevance
“…It has been suggested that numerous beneficial effects of exercise may be related to LTL [14,37,18] and to the modulation of the epigenome, which thereby may induce the adaptation of several stress-proteins/molecules response (i.e. antioxidants, heat shock proteins) already observed in different studies [16,47,6,7,9].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been suggested that numerous beneficial effects of exercise may be related to LTL [14,37,18] and to the modulation of the epigenome, which thereby may induce the adaptation of several stress-proteins/molecules response (i.e. antioxidants, heat shock proteins) already observed in different studies [16,47,6,7,9].…”
Section: Discussionmentioning
confidence: 99%
“…The ageing process is characterized by a reduction in motor capacity due to a gradual decrease of muscle strength and power [23]. It is known that resistance training can counteract physiological and biological age-related negative changes improving the performance of functional capacities and the stress oxidative/ protein response [45,51,6], but the proportion of elderly people who participate in this type of training protocol is currently low.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations